2020
DOI: 10.18632/aging.103838
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prognostic value of metabolism-related genes in gastric cancer

Abstract: Gastric cancer (GC) is one of the most commonly occurring cancers, and metabolism-related genes (MRGs) are associated with its development. Transcriptome data and the relevant clinical data were downloaded from The Cancer Genome Atlas and Gene Expression Omnibus databases, and we identified 194 MRGs differentially expressed between GC and adjacent nontumor tissues. Through univariate Cox and lasso regression analyses we identified 13 potential prognostic differentially expressed MRGs (PDEMRGs). These PDEMRGs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…It was significantly decreased in gastric tumor samples (Kropotova et al, 2013) and cervical squamous cell carcinoma samples (Peng et al, 2015). RDH12 was also one of the differentially expressed metabolism-related genes, and correlated with the prognosis of gastric cancer patients (Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was significantly decreased in gastric tumor samples (Kropotova et al, 2013) and cervical squamous cell carcinoma samples (Peng et al, 2015). RDH12 was also one of the differentially expressed metabolism-related genes, and correlated with the prognosis of gastric cancer patients (Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…INHBA, Inhibin-βA (INHBA), a ligand belonging to the transforming growth factorβ superfamily (Oshima et al, 2014), is associated with cell proliferation in various tumor types including colon adenocarcinoma (Lin et al, 2020a;Miao et al, 2020;Miyamoto et al, 2020), pancreatic cancer (Liu et al, 2020), gastric cancer as well as oral squamous cell carcinoma (Lin et al, 2020b). Many studies have demonstrated the prognostic role of INHBA in colon adenocarcinoma (Chen et al, 2020;Li et al, 2020; Miao Sun et al, 2020), and the role of INHBA in gastric cancer has been widely reported also. INHBA was highly expressed (Kaneda et al, 2011;Seeruttun et al, 2019;Zhang et al, 2010) and aberrantly methylated in gastric tumor samples, and high INHBA expression was associated with significantly poorer 5-year survival than low expression group (Katayama et al, 2017;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was significantly decreased in gastric tumor samples (Kropotova et al 2013) and cervical squamous cell carcinoma samples (Peng et al 2015). 2020:08:51875:2:1:NEW 19 Nov 2020) Manuscript to be reviewed RDH12 was also one of the differentially expressed metabolism-related genes, and correlated with the prognosis of gastric cancer patients (Wen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To build the prognostic model, univariate Cox regression analysis, LASSO regression, and multivariate Cox regression analysis were applied using R software (v3.6.1) based on the methodology of previously published studies [ 15 17 ]. Firstly, univariate analysis was performed to screen the significant DE immune genes based on the detected immune genes using the “survival” package.…”
Section: Methodsmentioning
confidence: 99%